2022
DOI: 10.1029/2021wr030185
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Flooding Mechanisms Across the Contiguous United States Through Interpretive Deep Learning on Representative Catchments

Abstract: The past decade has witnessed astonishing growth in the volume and diversity of data for water resource research, owing to the increasing number of installed observation sensor systems (McCabe et al., 2017) and the latest crowdsourcing and opportunistic sensing technologies (Jiang et al., 2019). A new challenge arising in this context is extracting information and knowledge from the data deluge (Reichstein et al., 2019). The concept of data mining, which aims to elicit implicit relationships and structures hid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…However, the DRB is a rain‐dominated system where near‐term soil saturation, precipitation, and air temperature drive key hydrological factors like stream temperature and discharge. Although work done in more snow dominated catchments has shown that LSTMs can learn long‐term snow‐water‐storage dynamics (Jiang et al., 2022), other antecedent meteorological variables generally lose their autocorrelation with hydrological variables beyond 30 days prior to the target conditions (Khanal et al., 2019). It is possible that the LSTM within RGCN is learning relationships between shallow‐groundwater and meteorological drivers, which could influence stream temperature on the scale of ∼100 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, the DRB is a rain‐dominated system where near‐term soil saturation, precipitation, and air temperature drive key hydrological factors like stream temperature and discharge. Although work done in more snow dominated catchments has shown that LSTMs can learn long‐term snow‐water‐storage dynamics (Jiang et al., 2022), other antecedent meteorological variables generally lose their autocorrelation with hydrological variables beyond 30 days prior to the target conditions (Khanal et al., 2019). It is possible that the LSTM within RGCN is learning relationships between shallow‐groundwater and meteorological drivers, which could influence stream temperature on the scale of ∼100 days.…”
Section: Discussionmentioning
confidence: 99%
“…Notice however that pursuing this direction may be subject to an “accuracy‐interpretability” dilemma that has been suggested to arise from a perhaps irreconcilable conflict between a model's predictive accuracy and the possibility of understanding its behaviors (Florez‐Lopez & Ramon‐Jeronimo, 2015). It would be valuable to devote more attention to investigating the use of DL interpretation methods to facilitate AI‐assisted scientific discovery (Jiang et al., 2022). By doing so, the advances in AI might more properly be able to leverage existing theories, helping to revolutionize the next generation of earth and environmental sciences (ESS) models in the near future (Fleming, Watson, et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al . (2022) uncovered the flooding mechanisms across the contiguous United States through interpretive deep learning on representative catchments.…”
Section: Discussionmentioning
confidence: 99%